Volume 3: Controls, Diagnostics and Instrumentation; Education; Electric Power; Microturbines and Small Turbomachinery; Solar B 2011
DOI: 10.1115/gt2011-45345
|View full text |Cite
|
Sign up to set email alerts
|

Improved Map Scaling Methods for Small Turbocharger Compressors

Abstract: Today engine performance simulations are essential in the preliminary design of turbocharged combustion engines, e.g. when matching the engine and the turbocharger. In order to optimize this matching process and to enable a preliminary selection of different turbocharger types and sizes, realistic modifications of the compressor and turbine maps are needed. This paper discusses several published approaches for compressor diameter scaling methods. In this context, an improved method to determine the efficiency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The compressors that were used in this study were derived from an Aeristech electric supercharger, which is able to reach a pressure ratio of 2.8 [15]. The experimental data that were used were adapted to this configuration by applying a reliable scaling method to adapt the compressor and the turbine to the size of the stack and the requirement of air mass flow [16][17][18].…”
Section: Compressor and Turbine Scaling Methodsmentioning
confidence: 99%
“…The compressors that were used in this study were derived from an Aeristech electric supercharger, which is able to reach a pressure ratio of 2.8 [15]. The experimental data that were used were adapted to this configuration by applying a reliable scaling method to adapt the compressor and the turbine to the size of the stack and the requirement of air mass flow [16][17][18].…”
Section: Compressor and Turbine Scaling Methodsmentioning
confidence: 99%
“…The laws can yield comparable results for differently sized turbomachinery; however, an exact match between the similar turbomachinery cannot be achieved [12]. Therefore, to simplify the scaling of turbomachinery, it can be assumed for small scaling factors of diameter that the Reynolds number can be free to vary and that the gas-specific properties of the flow are constant [13].…”
Section: Turbocharging Map Scalingmentioning
confidence: 99%
“…Comparing this assumption with Figure 2, it is clear that a significant change to the corrected shaft speed would be needed to affect the efficiency results. An analysis by Ernst et al [12] demonstrated that "for small trim variations (4%) the changes in pressure ratio and efficiency are negligible" and therefore scaling for efficiency should only be considered for large variations in trim (24%).…”
Section: Turbocharging Map Scalingmentioning
confidence: 99%
See 1 more Smart Citation
“…35,36 However, although the influence of the Reynolds number on pressure is small, 37 the effects on efficiency can be significant. 38,39 In order to address efficiency problems, Ernst et al 40 propose an empirical method for a centrifugal compressor.…”
Section: Introductionmentioning
confidence: 99%